Experimental biochemistry - Switzer, Robert L. (W. H. Freeman and Co., 1999)
This edition of "Experimental Biochemistry" is a perfect fit for today's biochemistry laboratory course. It provides comprehensive coverage of important techniques used in contemporary biochemical research and gives students the background theory they need to understand the nature of the experiments. Thoroughly classroom tested, the experiments incorporate the full range of biochemical materials in an attempt to simulate work in a research lab. In addition, a comprehensive appendix provides detailed procedures for preparation of reagents and materials, as well as helpful suggestions for the instructor.